Enhancing NVMe SSD Performance through Intelligent Data Placement: An Analysis of Implementation and Benefits - Kasthuri Theja Peduru, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Storage systems increasingly rely on NVMe SSDs for their superior performance characteristics, yet traditional static data placement strategies often fail to leverage their capabilities across diverse application workloads fully. This article comprehensively analyzes application-aware data placement in NVMe SSDs, exploring how workload-specific optimization can enhance storage performance. The core components of this article include workload characterization through read/write pattern analysis, strategic data placement optimization for both hot and cold data, and dynamic adaptation mechanisms for evolving workloads. This article addresses key implementation challenges such as processing overhead, protocol compatibility, and system scalability while highlighting potential benefits including improved I/O performance, reduced latency, and enhanced resource utilization. This article suggests that application-aware data placement represents a promising direction for optimizing NVMe SSD performance. However, careful consideration must be given to practical implementation constraints within existing NVMe standards and protocols.
Keywords: NVMe SSD; Application-Aware Storage; Data Placement Optimization; Workload Characterization; Storage Performance Management